Italy’s Banking System and the Coronavirus Crisis - Jürgen Matthes (Wirtschaftsdienst)
Abstract The Italian banking system has come through the coronavirus crisis quite well so far. Extensive government aid measures have contributed to this as well as pre-crisis reforms intended to eliminate legacy burdens from the euro debt crisis. These include the reduction of non-performing loans and the build-up of capital buffers. But in 2022, corporate insolvencies and problems with private customers could become a new test of endurance when state credit guarantees and moratoria gradually expire. Risks for the Italian banking system in the medium term are mainly due to the close ties between the state and the banks. A looming sovereign debt crisis thus threatens to quickly turn into a comprehensive economic crisis.